A case of Ewing-like sarcoma showing trilaminar differentiation after treatment - Mia C. Weiss; Marta Batus; Rahul B. Jadhav; Manuel Utset; Cristina O'Donoghue; Ira Miller (Elsevier, 2020)
Here we present a case of a 56 year old male with an Ewing-like bilateral retroperitoneal sarcoma with evidence of a EWSR1-POU5F1 fusion gene. Biopsy showed a high grade round cell sarcoma expressing strong membranous CD99 antigen. The tumor shrank considerably after extensive neoadjuvant chemo-radiation therapy. The resected specimens showed complete regression of the malignant component, with the residual tumor resembling ganglioglioma as well as of differentiated tumors of endoderm and mesoderm. While ganglioneuromatous differentiation of Ewing sarcoma has previously been reported, the other elements are a novel finding and may be attributed to the uncommon fusion transcript identified in this case and to the effect of therapy.